CHILD PARTICIPATION RIGHTS FRAMEWORKS AND THE ISLAMIC JURISPRUDENCE: RECONCILING CONVERGENCE AND IRRECONCILABLE DIVERGENCE - Haruna, Zakiyya (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
The paper examines the tension between the Convention on the Rights of the Child (CRC) and Islamic law with respect to children’s participation rights. While the CRC advances a model grounded in autonomy, self-expression, and individual freedoms, Islamic law embeds participation within a framework of parental authority, responsibility, and moral guidance. The paper using a doctrinal research methodology makes a comparative analysis to argue that the crux of the debate lies not in whether children may participate, but in how participation is structured: an almost unrestricted autonomy in the CRC versus a duty-oriented, guided participation in Islam. Under the Sharia, a pre-pubescent child lacks legal capacity to make consequential decisions; the expression of views is permitted but not codified as an enforceable right; and obedience to parents is foundational except where it entails sin. The paper finds that these differences yield divergent implications: freedoms of expression, religion, association, and privacy core to the CRC are circumscribed in Islam to safeguard spiritual and moral welfare. By highlighting these contrasts, the paper concludes that the study contributes to the discourse on reconciling international child rights frameworks with Islamic jurisprudence, clarifying both points of convergence and irreconcilable divergence.